Regulation of Francisella Tularensis Virulence - Dai, Shipan; Mohapatra, Nrusingh P.; Schlesinger, Larry S.; Gunn, John S. (Frontiers in Microbiology, 2011)
Francisella tularensis is one of the most virulent bacteria known and a Centers for Disease Control and Prevention Category A select agent. It is able to infect a variety of animals and insects and can persist in the environment, thus Francisella spp. must be able to survive in diverse environmental niches. However, F. tularensis has a surprising dearth of sensory and regulatory factors. Recent advancements in the field have identified new functions of encoded transcription factors and greatly expanded our understanding of virulence gene regulation. Here we review the current knowledge of environmental adaptation by F. tularensis, its transcriptional regulators and their relationship to animal virulence.